Group identity, empathy and shared suffering: understanding the ‘community’ impacts of anti-LGBT and Islamophobic hate crimes - Walters, Mark Austin (International review of victimology, 2020)
This article examines the indirect impacts of hate crimes on lesbian, gay, bisexual and transgender and Muslim communities in the United Kingdom. Based on 34 qualitative interviews, we explore both the perceived meaning of ‘community’ in the context of targeted victimization and the emotional and behavioural effects that anti-lesbian, gay, bisexual and transgender and Islamophobic hate crimes have on other members of the victim’s group. Building on previous quantitative data undertaken as part of a larger programme of research, this study helps to explain how and why hate crimes have significant indirect consequences on two distinct but commonly targeted communities. The focus on lesbian, gay, bisexual and transgender and Muslim communities allowed us to draw out similarities and commonalities across different groups, further enhancing the understanding of the impacts of hate crime. In particular, the article highlights how for many lesbian, gay, bisexual and transgender and Muslim people feelings of anger and anxiety about hate crimes were linked to enhanced levels of empathy towards those that they share a group identity with. These empathic bonds often gave rise to a sense of ‘shared suffering’, with participants frequently feeling connected to group members worldwide through their common experiences of hate and prejudice. Although group identity was important to many participants’ sense of belonging to lesbian, gay, bisexual and transgender or Muslim communities, it was clear that the most profound impacts of hate crime were experienced when incidents occurred within someone’s local area. This highlighted the importance of location as a key variable in understanding both the meaning of ‘community’ and the indirect impacts of hate crime.